The literary sections of the newspaper “Ρωμιοσύνη” (“Romiosini”) 1997-2006 - Polo, Olieta; Sulaj, Manjola (International Journal of Psychosocial Rehabilitation, 2020)
In this article we aim to highlight the literary sections of the Ethnic Greek Minority in Albania of the newspaper “Ρωμιοσύνη” (“Romiosini”) published during 1997-2006 after the fall of the Communist dictatorship in Albania (1945-1990). In the literary sections of this newspaper, especially during the second decade of its publication, were included many qualitative creations of the literary works of the writers belonging to the Ethnic Greek Minority in Albania. We will deal mainly with the poems and the stories published in the newspaper, bringing concrete titles and general characteristics of these literary types, which had their artistic and aesthetic values, without the dictatorship artistic shortcomings that derived from the ideological restrictions of the ruling communist party. These creations with their values further enriched the tradition and the culture of the Ethnic Greek Minority and as such deserve to take their place in the studies of the literary criticism.